Rifampicin liposomes loaded on calcium phosphate cement scaffold constructed using 3D printing technology for sustained drug release - Jie Jin; Mingfeng Zheng; Xinjun Cai; Xudong Fan (Brazilian Journal of Pharmaceutical Sciences)
Abstract Rifampicin (RFP) is used for the treatment of chronic bone tuberculosis owing to its powerful and wide spectrum antibacterial activities. However, effective concentrations of RFP required to treat bone tuberculosis are maintained for a short time in vivo, and adverse reactions and bone defects may occur after surgery. Therefore, the construction of a new drug delivery system to overcome these problems is required. In this study, we designed, constructed, and demonstrated the applicability of a calcium phosphate cement scaffold loaded with RFP liposomes for the treatment of bone tuberculosis. RFP liposomes were prepared using a film dispersion method. The preparation method was optimized using the encapsulation rate as an indicator and the morphology, mean particle size, zeta potential, encapsulation rate, and drug loading of RFP liposomes were characterized. Calcium phosphate cement scaffolds were constructed using 3D printing technology and used as RFP liposome carriers for sustained-release drug delivery. Finally, some of the properties were verified in vivo through experiments in rabbits. The results indicated that composite scaffolds can provide sustained drug release and are a promising treatment option for bone tuberculosis.